2016
DOI: 10.1186/s11671-016-1750-9
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Peel Waste for the Production of ZnO Nanoparticles and its Toxicological Efficiency, Antifungal, Hemolytic, and Antibacterial Activities

Abstract: Zinc oxide (ZnO) nanoparticles (NPs) are important materials when making different products like sun screens, textiles, and paints. In the current study, the photocatalytic effect of prepared ZnO NPs from Moringa oleifera (M. oleifera) was evaluated on degradation of crystal violet (CV) dye, which is largely released from textile industries and is harmful to the environment. Preliminarily, ZnO NP formation was confirmed using a double beam ultraviolet visible (UV-Vis) spectrophotometer; further, the NP size wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(33 citation statements)
references
References 30 publications
(31 reference statements)
1
27
0
Order By: Relevance
“…Green chemistry approaches are especially useful for the generation of metallic nanoparticles (NPs), which have nanometric structures that effectively and efficiently address concerns in both health care and industrial applications. [33][34][35] Therefore, these approaches offer the chance to use living organisms (such as bacteria, 36 human cells, 37,38 fungi, 39 or plants 40,41 ) as well as dietary and organic natural compounds (such as coffee, 42 tea, or honey extracts 43 ) or biological waste materials produced from industrial alimentary plants, 44 to naturally synthesize NPs. These nanostructures exhibit antibacterial and/or anticancer properties and can be used as drug delivery carriers and in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Green chemistry approaches are especially useful for the generation of metallic nanoparticles (NPs), which have nanometric structures that effectively and efficiently address concerns in both health care and industrial applications. [33][34][35] Therefore, these approaches offer the chance to use living organisms (such as bacteria, 36 human cells, 37,38 fungi, 39 or plants 40,41 ) as well as dietary and organic natural compounds (such as coffee, 42 tea, or honey extracts 43 ) or biological waste materials produced from industrial alimentary plants, 44 to naturally synthesize NPs. These nanostructures exhibit antibacterial and/or anticancer properties and can be used as drug delivery carriers and in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminarily, UV–Vis spectroscopic analysis was utilized for determination of Gd 2 O 3 NPs formation. Further, the reaction mixture was centrifuged thrice as we mentioned in our earlier reports . The collected particles were calcinated at 300°C and obtained NPs were subjected to the different characterizations …”
Section: Methodsmentioning
confidence: 99%
“…Further, the reaction mixture was centrifuged thrice as we mentioned in our earlier reports. 13 The collected particles were calcinated at 300 C and obtained NPs were subjected to the different characterizations. 14 NPs has been optimized using three factors such as M oleifera peel extraction concentration, Microwave Wattz and time.…”
Section: Microwave-assisted Gd 2 O 3 Nps Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The recent literature survey revealed that ZnO nanoparticles as heterogenous catalyst as received much attention due to the advantages: that is, minimum execution time, easy workup procedure, low corrosion, economically cheap chemical, commercially available, easily synthesized , and recycling of it. In recent years, ZnO nanoparticles have excellent potential in expressing abundant biological properties such as antimicrobial , antioxidant, anticancer, and other activities . ZnO nanoparticles were also suggested as good photocatalytic agents .…”
Section: Introductionmentioning
confidence: 99%